Analysis and modeling of recent business failures in Greece - Theodossiou, Panayiotis; Papoulias, Costas (My University, 1992)
This paper provides an analysis of recent business failures in Greece and presents models for detecting financially distressed firms. Logit, probit, linear probability model, and linear discriminant analysis are used for developing these models. Potential users of the models include the banking system, corporate creditors, regulatory agencies, and investors in Greece, the European Economic Community, the USA, and other countries. These models expand the tools used by international and domestic investors to measure Greek firms' risk of insolvency.